Recycling WEEE: Extraction and concentration of silver from waste crystalline silicon photovoltaic modules. (November 2016) - Dias, Pablo; Javimczik, Selene; Benevit, Mariana; Veit, Hugo; Bernardes, Andréa Moura
Highlights: Silver from silicon PV modules was mapped and characterized. Silver from silicon PV modules was quantified and compared to justify its recovery. The proposed silver extraction route concentrates 94% of PV modules' silver. A route involving a pyrolysis process step was testes and compared. The pyrolysis does not assist the extraction and recovery of silver in PV modules. Abstract: Photovoltaic modules (or panels) are important power generators with limited lifespans. The modules contain known pollutants and valuable materials such as silicon, silver, copper, aluminum and glass. Thus, recycling such waste is of great importance. To date, there have been few published studies on recycling silver from silicon photovoltaic panels, even though silicon technology represents the majority of the photovoltaic market. In this study, the extraction of silver from waste modules is justified and evaluated. It is shown that the silver content in crystalline silicon photovoltaic modules reaches 600 g/t. Moreover, two methods to concentrate silver from waste modules were studied, and the use of pyrolysis was evaluated. In the first method, the modules were milled, sieved and leached in 64% nitric acid solution with 99% sodium chloride; the silver concentration yield was 94%. In the second method, photovoltaic modules were milled, sieved, subjected to pyrolysis at 500 °C and leached in 64% nitric acid solution with 99% sodium chloride; the silver concentration yield was 92%. The first method is preferred as it consumes less energy and presents a higher yield of silver. This study shows that the use of pyrolysis does not assist in the extraction of silver, as the yield was similar for both methods with and without pyrolysis.